CD4 Count and Viral Load Differences in HIV Patients with and without Infectious Posterior Uveitis at a Tertiary Hospital in Indonesia - Shofa Annesa Hidayat; Ismi Zuhria; Muhammad Vitanata Arfijanto; Reni Prastyani (Current Internal Medicine Research and Practice Surabaya Journal)
Introduction: The human immunodeficiency virus (HIV) compromises the immune system, making the monitoring of cluster of differentiation (CD4) counts and viral loads critical for assessing disease progression and opportunistic infection risks. Eye-related manifestations, such as uveitis, are common among HIV patients. The purpose of this study was to investigate the differences in CD4 count and viral load between HIV patients with infectious posterior uveitis and those without at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia.